United States. Legation (Austria) records - United States. Legation (Austria)
ALS (1839 April 10) from John Randolph Clay to Stephen Pleasonton; receipt (1839 January 1) from John Cuthbert to Henry Augustus Philip Muhlenberg; receipt for postage (1839 January) from John Miller to Muhlenberg; report (1839 December 31) from John George Schwartz to the legation; and account book (1840 January 1) kept by Clay listing contingent expenses of the legation headquarters in Vienna.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Clay, John Randolph, -- 1808-1885 -- Correspondence; Miller, John, -- active 1839.; Muhlenberg, Henry Augustus Philip, -- 1782-1844.; Pleasonton, Stephen, -- -1855 -- Correspondence; Schwartz, John George; Diplomatic and consular service, American -- Austria; Austria -- Foreign relations -- United States; United States -- Foreign relations -- Austria; Vienna (Austria) -- History -- 19th century